Soot and house dust mite allergen cause eosinophilic laryngitis in an animal model. (21st July 2015) - Belafsky, Peter C.; Peake, Janice; Smiley‐Jewell, Suzette M.; Verma, Sunil P.; Dworkin‐Valenti, James; Pinkerton, Kent E.
Abstract : Objectives/Hypothesis: Chronic laryngitis (CL) is common and costly. One of the most common causes of CL is thought to be laryngopharyngeal reflux, although a significant percentage of individuals fail to get better with acid suppressive therapy. The role of other potential causes of CL such as allergy and environmental pollution has not been thoroughly investigated. Purpose: To evaluate the association between iron soot, house dust mite allergen (HDMA), and CL in an established animal model. Methods: Twenty‐four guinea pigs were separated into four 6‐week exposure groups: 1) saline (allergen control) + filtered air (pollution control); 2) HDMA ( Dermatophygoides farinae ) + filtered air; 3) saline + combustion particulates; or 4) HDMA + combustion particulates. The primary outcome measure was mean eosinophil profile (MEP) in glottic, subglottic, and trachea epithelium and submucosa. Results: The combination of iron soot and HDMA caused eosinophilia (elevated MEP) in the glottic ( P  < 0.06), subglottic ( P  < 0.05), and trachea ( P  < 0.05) submucosa and epithelium ( P  < 0.05). Conclusion: The combination of HDMA and iron soot resulted in laryngeal eosinophilia in an established guinea pig model of CL. The data support the notion that factors other than reflux may cause CL. Further investigation into eosinophilic laryngitis as a distinct clinical entity caused by exposure to environmental allergen and pollution is warranted. Level of Evidence: N/A. Laryngoscope, 126:108–112, 2016